High-output chyloperitoneum following laparoscopic Nissen fundoplication treated with retrograde transvenous thoracic duct embolization - Gernot Rott; Frieder Boecker (CVIR Endovascular, 2020)
Abstract Background Iatrogenic injury of the thoracic duct with clinical significant chyloperitoneum is a rare complication of abdominal surgery. Chyloperitoneum following laparoscopic Nissen fundoplication has been described in a few cases only. Most interventionists use the antegrade transperitoneal approach for thoracic duct embolization. Case presentation A 61-year-old woman had been operated with laparoscopic Nissen fundoplication and hiatoplasty. A few weeks later she presented with high-output chyloperitoneum due to large leakage of the proximal thoracic duct. Conservative treatment and conventional transnodal lymphangiography did not result in a significant improvement. Thoracic duct embolization via retrograde transvenous access was challenging but both technically and clinically successful. Conclusion To the best of our knowledge, this is the first case-report about thoracic duct embolization with retrograde transvenous access in the rare situation of chylous ascites following laparoscopic fundoplication. Thoracic duct embolization with the seldom used retrograde transvenous access may be the more physiologic and safer route in doing this and might be used as treatment of first choice.